Africa's Urban Risk and Resilience. (December 2017) - Fraser, Arabella; Leck, Hayley; Parnell, Sue; Pelling, Mark
Abstract: The literature on disaster risk and its reduction in Africa's urban centres remains limited, despite evidence of disaster risks increasing with urban growth. This Special Issue brings together new synthetic reviews, detailed empirical case studies and practitioner and expert commentary to highlight the multiple ways in which risk and urban development are co-evolving in the region. It broadens understanding about the nature, scale and distribution of urban risks, examining relationships between everyday and disaster risks across scales. Papers in the Issue also interrogate the role of governance processes in driving risks, including strong recognition of the role of social institutions where formal governance structures are incomplete, and the underlying knowledge and power relationships that shape urban risk management. Potential learning from innovation is discussed in the light of the rise of resilience paradigms in urban development as well as the ongoing embedding of international agreements in local agendas that offer the potential to drive forward risk-sensitive urban development pathways.